Residential self-selection and the relative importance of travel considerations in the residential choice of a car-reduced neighbourhood - Klein, Marcus; Klinger, Thomas; Lanzendorf, Martin (Transportation research. Part A, Policy and practice, 2024)
•Travel preferences are important in choosing to live in a car-reduced neighbourhood.•Residential self-selection is higher among individuals with strong car orientation.•RSS to car-reduced neighbourhood exists even in highly priced real estate market.•Living in a car-reduced neighbourhood leads to a decrease in car use. Car-reduced neighbourhoods are an urban planning tool to limit the increase in motorised traffic due to urban growth by making car ownership and use less attractive for the inhabitants. Since car-reduced living appeals more to some people than others, car-reduced neighbourhoods may be subject to residential self-selection (RSS). RSS indicates that individuals choose residential areas that support pre-existing travel attitudes and preferences, and, in consequence, that their travel behaviour is not solely the result of the built environment. Many studies on RSS operationalise self-selection effects using travel-related attitudes. In contrast, we assume that travel considerations in residential location choice (TCRC) are more precise for this purpose. While attitude refers to a mental state towards a travel mode, e.g. a personal affection for cycling, TCRC describes an actual desire to live in an area with, for example, street layouts that facilitate cycling. Drawing on a sample of 339 recently relocated inhabitants of a car-reduced neighbourhood in Darmstadt, Germany, we first identify the importance of TCRC in choosing this neighbourhood relative to other residential considerations. We find that TCRC have less influence compared to factors such as house size and price. However, a comparison of individuals with low and high car orientation reveals that the former prioritise car-reduced designs more when selecting a neighbourhood. Second, we find that new residents’ car use decreases after relocating, while carsharing use increases. Third, we find no significant difference between attitudes and TCRC when measuring RSS in our behaviour change models. In terms of policy implications, the further development of car-reduced neighbourhoods will (i) trigger an increase in the use of sustainable modes among new residents and (ii) make it easier for people who already rarely drive to maintain their car independence.